Analysis of Income and Costs of Business Activity Development at the Business Development Center (P2B) of Makassar State Islamic University - Marsuni, Nur Sandi; Rismawati, Rismawati (Jurnal Ekonomi Balance, 2018)
The type of research employed a quantitative descriptive analysis method. The data was collected through in-depth interview with the canteen’s user, the canteen’s management and the leader of Pusat Pengembangan Binis (P2B), observation and documentation. The subject of this research consists 2 canteen’s users, staff and of Pusat Pengembangan Binis (P2B). The data analysis was employed based on procedure of data analysis that consisted of steps data collection, reduction, display and conclusion drawing/verifying. The result of study about the calculations and data collection of income and the cost of business units canteen on Pusat Pengembangan Bisnis (P2B) showed that the convenience of the users of the canteen need to be considered to make improvements to building facilities inadequate, and the merchants of the wild that have sprung up in the heart of the campus of UIN Alauddin Makassar need to put in order with how to set up a place for their use, so that can add to the income on Pusat Pengembangan Bisnis (P2B) of UIN Alauddin Makassar.